2015
DOI: 10.1093/ndt/gfv225
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid is not associated with decline in renal function or time to renal replacement therapy initiation in a referred cohort of patients with Stage III, IV and V chronic kidney disease

Abstract: UA is not associated with the rate of decline in renal function or time to start of RRT in Stage III, IV and/or V CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 56 publications
1
32
0
2
Order By: Relevance
“…Although some studies showed no association between hyperuricemia and the progression of CKD [1014], other studies found hyperuricemia may hasten the failing of renal function measured by eGFR or increase the risk of developing ESRD(Table 4) [3142]. Among 63,758 subjects with baseline eGFR ≥ 60 ml/min/1.73 m 2 , the subjects with hyperuricemia had an average annual decline of eGFR of 2.5 ± 9.5 mL/min/1.73 m 2 , that was almost twice faster than those of patients with normal uric acid levels [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies showed no association between hyperuricemia and the progression of CKD [1014], other studies found hyperuricemia may hasten the failing of renal function measured by eGFR or increase the risk of developing ESRD(Table 4) [3142]. Among 63,758 subjects with baseline eGFR ≥ 60 ml/min/1.73 m 2 , the subjects with hyperuricemia had an average annual decline of eGFR of 2.5 ± 9.5 mL/min/1.73 m 2 , that was almost twice faster than those of patients with normal uric acid levels [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent meta-analysis found that elevated serum UA levels were associated with incident CKD [9], the role of UA in CKD progression is still debating. For instance, results from a large cohort of the Swedish Renal Registry showed neither the rate of estimated glomerular filtration rate (eGFR) decline nor rapid progression to end stage renal disease (ESRD) was associated with serum UA levels in patients with CKD stage 3 to 5 [10]. This finding is concordant with some recent observational studies of patients with a wide range of renal function at baseline in the U.S. [11], Taiwan [12], and Europe (Germany, Austria, south Tyrol, and Netherlands)[13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…The association between high serum uric acid (UA) and progression of CKD was suggested by many studies of stage G1 and G2 [97][98][99] . A more recent study denied this association in stages G3, 4 and 5 [100] . On the other hand, hyperuricemia was found as independent risk factor for CKD progression in children and adolescents [101] .…”
Section: Pathogenesismentioning
confidence: 92%
“…Можна розгля-нути, наприклад, результати аналізу історичної ко-горти японських чоловіків, які пройшли медичне обстеження в період з 1998 по 2007 р. Включені були учасники, які мали вихідні обстеження, знаходилися під наглядом не менше 1 року і були розподілені від-повідно до вихідної функції нирок. Ниркова функ-ція була класифікована як збережена (розрахована ШКФ більше 90 мл/хв/1,73 м 2 ) або помірно зниже-¹ 1 (15) Аналіз даних Шведського ниркового реєстру хронічної хвороби нирок SRR-CKD, в якому було проаналізовано результати обстежень 2466 пацієн-тів, оглянутих з 2005 по 2011 р., із середнім часом спостереження 26 місяців, показує відсутність ста-тистично значимої зміни в середньому зниженні ШКФ при кожному збільшенні рівня сечової кис-лоти на 1 мг/дл (59 мкмоль/л) порівняно з вихідним рівнем, а також відсутність зв'язку між збільшенням рівня сечової кислоти на 1 мг/дл (59 мкмоль/л) по-рівняно з вихідним рівнем і початком нирково-за-місної терапії у пацієнтів з ІІІ-V стадіями хронічної хвороби нирок [15].…”
Section: Looking At the Problemunclassified